Impaired Olfaction and Risk for Delirium or Cognitive Decline After Cardiac Surgery - Brown, Charles H. (J Am Geriatr Soc, 2015)
SUMMARY STATEMENT: Impaired olfaction, identified in 33% of patients undergoing cardiac surgery, was associated with the adjusted risk for postoperative delirium but not cognitive decline. OBJECTIVES: The prevalence and significance of impaired olfaction is not well characterized in patients undergoing cardiac surgery. Because impaired olfaction has been associated with underlying neurologic disease, impaired olfaction may identify patients who are vulnerable to poor neurological outcomes in the perioperative period. The objective of this study was to determine the prevalence of impaired olfaction among patients presenting for cardiac surgery and the independent association of impaired olfaction with postoperative delirium and cognitive decline. DESIGN: Nested prospective cohort study SETTING: Academic hospital PARTICIPANTS: 165 patients undergoing coronary artery bypass and/or valve surgery MEASUREMENTS: Olfaction was measured using the Brief Smell Identification Test, with impaired olfaction defined as an olfactory score < 5(th) percentile of normative data. Delirium was assessed using a validated chart-review method. Cognitive performance was assessed using a neuropsychological testing battery at baseline and 4–6 weeks after surgery. RESULTS: Impaired olfaction was identified in 54 of 165 patients (33%) prior to surgery. Impaired olfaction was associated with increased adjusted risk for postoperative delirium (relative risk [RR] 1.90, 95% CI 1.17–3.09; P=0.009). There was no association between impaired olfaction and change in composite cognitive score in the overall study population. CONCLUSION: Impaired olfaction is prevalent in patients undergoing cardiac surgery and is associated with increased adjusted risk for postoperative delirium, but not cognitive decline. Impaired olfaction may identify unrecognized vulnerability for postoperative delirium among patients undergoing cardiac surgery.